Microbiological properties of soils are sensitive to changes provided by organic cultivation of banana ‘BRS Princesa’ in the semi-arid region - Luana Silva Cerqueira; Aldo Vilar Trindade; Luciano Ricardo Braga Pinheiro; Carla da Silva Sousa (Acta Scientiarum: Biological Sciences, 2023)
Soil microbiota has a key role in the dynamics of natural and agro-ecosystems and is sensitive to changes in these environments. This study evaluated changes in the microbiological properties of soils under an organic production system of banana ‘BRS Princesa’ (Musa spp.). The experimental design consisted of completely randomized blocks, with four replications. Treatments consisted of 1) soil cover with green manure and agricultural gypsum at a dose of 2,820 kg ha−1, 2) soil cover with green manure without gypsum application, 3) soil cover with weeds and agricultural gypsum at a dose of 2,820 kg ha−1, 4) soil cover with spontaneous plants without gypsum application, and two controls: 5) soil under native Caatinga and 6) soil under regenerating forest (capoeira). The evaluated properties were β-glucosidase, arylsulfatase, acid phosphatase, fluorescein diacetate hydrolysis activities (FDA), carbon and phosphorus contents in microbial biomass, basal soil respiration, microbial and metabolic quotients, and arbuscular mycorrhizal fungi spore density. Soil samples were collected from the 0–0.20m depth layer in two seasons. No parameter could distinguish the treatments. Spontaneous plants provided conditions equivalent to those under green manure. Agricultural gypsum application also did not influence the microbial biomass and microbiota activity, in the analyzed soil depth. However, β-glucosidase and arylsulfatase activities, the carbon content in microbial biomass, and metabolic and microbial quotients were sensitive to land-use changes and could distinguish areas under organic cultivation from those under native vegetation. Therefore, these properties can be considered good indicators for monitoring the quality of these soils. Furthermore, microbial communities of soils under organic cultivation responded with arylsulfatase activity corresponding to that found in soils under regenerating forest, which may indicate that organic management tends to provide the microbiota with a condition similar to that found under situations that are little disturbing to edaphic living.